ANALISIS RISIKO DAN BAHAYA PADA AREA PENAMBANGAN MENGGUNAKAN METODE HAZARD IDENTIFICATION, RISK ASSESSMENT, AND RISK CONTROL (HIRARC) SITE BANKO BARAT PT BUKIT ASAM TBK SUMATERA SELATAN - M. Fitra Wahyudi; Suhardiman Gumanti; Ahmad Husni (Jurnal Humaniora & Sosial Sains, 2025)
This study aims to examine the potential hazards and occupational risks associated with coal mining, with particular emphasis on the loading, hauling, and dumping processes at the PT Bukit Asam Tbk site in South Sumatra. Due to the complex working environment, the use of heavy equipment, and unstable geological conditions, the mining industry is a high-risk occupational industry for occupational accidents and health problems. This study used field observations, primary and secondary data collection, and analysis of employee questionnaires. The results showed that the hauling area has the highest hazard potential, while the loading and dumping area has the lowest. Collisions between parts, overturning of heavy equipment, and exposure to dust are some of the most common occupational accidents. The main causes of risk were identified as unstable road conditions, failure to use personal protective equipment (PPE), and failure to comply with standard operating procedures (SOPs). Therefore, the implementation of an OHS management system, regular training, and routine safety inspections are essential for risk control. It is hoped that this study will contribute to improving occupational safety in mining.